Grief Demystified : an Introduction. - Lloyd, Caroline (Jessica Kingsley Publishers, 2017)
Telling you what you need to know about grief, this book is the perfect introduction for the lay reader who works with the bereaved. Giving the basics of modern grief theory, tips on what to say to someone in grieving and much more, it is a must read for anyone who works with the bereaved.